CONTRACEPTION IN PATIENTS WITH OBESITY - I. O. Makarov; E. I. Borovkova (IRBIS LLC, 2016)
The article presents modern possibilities of the use of hormonal contraceptives in the form of combined estrogen-gestagenic agents, of gestagenic contraceptives, intrauterine equipment, implants and adhesive bandages. Discussedmainissuesof efficiency, safety and acceptability of the use of these funds in the high-risk group for the development of complications.